Comparative Spiritual Emotional Intelligence to Organizational Citizenship Behavior (Study in Employee of Telkomsel Distribution Center-TDC at Salatiga and Ungaran Branch Offices) - Imas Rahmasari; Rr Wuri Arenggoasih; Nova Mega Pertiwi (IJIP : Indonesian Journal of Islamic Psychology, 2022)
Abstract The success of the company is undoubtedly the result of satisfying employee efforts. As a company, with branches in almost every city, Telkomsel Distribution Center-TDC has one of the effective components is behavior outside of formal requirements by employees that can reach the target, called OCB. The attribution theory explains the causes of a person's behavior (internal factors), one of which is ESQ. As quantitative research, this study aims to determine the effect of ESQ on OCB in Salatiga and Ungaran TDC employees, which is then carried out a comparative analysis on 53 employees as a whole sample (saturation sampling technique). The results show a significant effect of ESQ on employee OCB is 39.3% in Salatiga TDC, while Ungaran's TDC is 61.7%. Then, the comparison results obtained an average similarity of ESQ and OCB variables between Salatiga and Ungaran TDC, with a significance value of 0.108 for ESQ and 0.363 for OCB. AbstrakKeberhasilan perusahaan tidak diragukan lagi merupakan hasil dari usaha karyawan yang memuaskan. Sebagai perusahaan yang memiliki cabang hampir di setiap kota, Telkomsel Distribution Center-TDC memiliki salah satu komponen efektif yaitu perilaku di luar persyaratan formal karyawan yang dapat mencapai target, yang disebut OCB. Teori atribusi menjelaskan penyebab terjadinya perilaku seseorang (faktor internal), salah satunya adalah ESQ. Sebagai penelitian kuantitatif, penelitian ini bertujuan untuk mengetahui pengaruh ESQ terhadap OCB pada pegawai TDC Salatiga dan Ungaran, yang kemudian dilakukan analisis komparatif terhadap 53 pegawai sebagai sampel keseluruhan (teknik sampling jenuh). Hasil penelitian menunjukkan pengaruh signifikan ESQ terhadap OCB karyawan sebesar 39,3% di TDC Salatiga, sedangkan TDC Ungaran sebesar 61,7%. Kemudian dari hasil perbandingan diperoleh rata-rata kesamaan variabel ESQ dan OCB antara TDC Salatiga dan Ungaran, dengan nilai signifikansi 0,108 untuk ESQ dan 0,363 untuk OCB.Kata Kunci: karyawan; kecerdasan emosional spiritual; organizational citizenship behavior